Estimating parasitic loads related to brine production from a hot sedimentary aquifer geothermal project: A case study from the Clarke Lake gas field, British Columbia. (June 2020) - Banks, Jonathan; Rabbani, Arif; Nadkarni, Kabir; Renaud, Evan
Abstract: Geothermal power development requires significant to decreasing parasitic loads. Developers often ignore the pumping power necessary to circulate geothermal fluids, leading to an erroneous calculations of power potential. We present a workflow for calculating the pumping power for wells in a geothermal field and apply it to the Clarke Lake Gas field in the northeast British Columbia as a case study. The combination of a thick, highly porous formation and subsurface water temperatures in excess of 110 °C make this field one of the most promising areas for geothermal development in Western Canada. The pumping parasitic loads for the field, calculated from the stabilized reservoir pressure and hydrogeological properties listed for the wells, varies significantly with reservoir temperature and depth from the ground surface to the water column. The parasitic loads related to production pumping requirements range from 2% to 60% with a mean of 21% and a standard deviation of 14%. We then revised previous gross power potential estimates for the Clarke Lake gas field base on our calculated parasitic loads. Our results suggest that, despite significant parasitic loads, the Clarke Lake gas field could still net tens of megawatts of electrical power over a multi-decade production period. Highlights: Parasitic loads are often overlooked when estimating geothermal resources. We present a method for calculating parasitic loads in low-T geothermal systems. The method is applied to a depleted gas reservoir in NE British Columbia. Parasitic loads range from 2% to 60% with a mean of 21% ± 14%.